Regional Agriculture in Romania: A Quantitative Assessment - EMILIA BĂLAN (Global Economic Observer)
In last decade, the Romania’s regional agriculture has become the main driver of development through absorption of EU funds. According to official data of the Ministry of Agriculture and Rural Development, Romania has reached 84% (or 12.85 billion euros) in the field of EU absorption funds for agriculture and rural development programmes during 2007-2013. According to the latest EU statistics, in Romania agricultural sector has a high importance in ensuring income through self-employment, while diversification of rural economy remains challenging. Most people engaged in agriculture are self-employed and agriculture accounts for only 3.2% in the total number of the employees in the Romanian economy. The paper intends to assess the stage of development of agriculture in Romania by regions, based on a quantitative analysis, using both national and European statistics. The results of this article show regional disparities of agricultural development in Romania and the need for central authorities to diminish the differences between macro regions in the agriculture field.